Improved stability of up-flow anaerobic sludge blanket reactor treating starch wastewater by pre-acidification: Impact on microbial community and metabolic dynamics. (April 2021) - Wu, Jiang; Jiang, Bo; Kong, Zhe; Yang, Chongyang; Li, Lu; Feng, Bo; Luo, Zibin; Xu, Kai-Qin; Kobayashi, Takuro; Li, Yu-You
Graphical abstract: Highlights: Two UASB processes were investigated by continuously feeding with starch wastewater. The predominant methanogenic pathways in the two processes were different. Different surface attachments were observed on the granules in the two processes. The microbial function of the one-stage UASB shifted to hydrogen fermentation. Abstract: Poor processing stability has been cited as the fatal shortcoming of the up-flow anaerobic sludge blanket (UASB) reactor treating starch wastewater (SW). In this study, the SW treatment performance in a one-stage UASB reactor and a pre-acidification equipped UASB process were evaluated together with the microbial dynamics. The results revealed that the pre-acidification provided improvements in terms of the substrate utilization diversity and the stability of the microbial community structure on the UASB reactor. Anaerolineaceae / Methanosaeta was the core functional microbiota in the pre-acidification equipped UASB reactor, indicated the superior abilities on the acetogenic methanogenesis of granules. The genus of Methanobacterium, a hydrogenotrophic methanogen was dominant in the archaeal community in the one-stage UASB reactor. The granules performed very strong hydrogen affinity in methane production, a small amount of propionate was detected in the effluent. These were abnormal, which suggested the high hydrogen turn-over rate in the one-stage UASB reactor.